Takotsubo syndrome in a heart transplant recipient with poor cardiac sympathetic reinnervation - Ryo Miyake; Kisho Ohtani; Toru Hashimoto; Ryoko Yada; Tasuku Sato; Yoko Shojima; Shunji Hayashidani; Taiki Higo; Hiroyuki Tsutsui (ESC Heart Failure)
Abstract Takotsubo syndrome (TTS), also referred to as stress cardiomyopathy, is characterized by transient left ventricular apical ballooning in the absence of obstructive coronary artery disease. Catecholamine‐induced cardiac injury or vasospasm has been implicated in this pathophysiology. We present a case of a 67‐year‐old man 10 years after heart transplantation diagnosed with TTS. Sympathetic reinnervation could not be detected by iodine‐123 meta iodobenzylguanidine uptake, suggesting that TTS can occur in the absence of functional sympathetic nerve systems reconstruction.